The Role of Export and Terms of Trade for an Economy with Resource Dependence, Case of Algeria - Touitou, Mohammed; Djellit, Tahar; Boudeghdegh, Ahmed (European Journal of Sustainable Development, 2018)
The paper analyses the impact of foreign trade to GDP growth in Algeria on the basis of cointegration analysis. The aim of the paper is to assess causal relations between exports, oil prices, terms of trade and economic growth. The literature discusses different options: a positive unidirectional relation from exports growth and terms of trade improvement to economic growth (export-led growth), opposite relation from economic growth to export growth and bidirectional causal relations between indicators, negative effects of exports are also discussing. In this paper we firstly provide a statistical overview of the dynamics of foreign trade over the last decade and calculate terms of trade index. Secondly, we conduct an econometric analysis of the interdependence of indicators: GDP growth, exports, terms of trade and the price of oil in terms of vector error correction model (VECM). We consider two model specifications for quarterly and annual data, perform “Granger causality” test for the time series data. We found positive short-term and long-term dependence of economic growth on export and oil prices and long-term dependence on the terms of trade, bidirectional relations was not identified. The results confirm the high dependence of the economy on the external sector and export-led growth hypothesis. Thus, exports and foreign trade should be considered as a source of economic growth for the country, the external sector is important to consider when building the economic growth forecast and modeling of economic policy. Keywords: Economic growth; Algeria, VECM, Foreign trade.